Revealing the Escape Dynamics in a Hamiltonian System with Five Exits (Journal of Nonlinear Modeling and Analysis, 2024)
The scope of this work is to reveal, by means of numerical methods, the escape process in a Hamiltonian system with five exits which describes the problem of rearrangement multichannel scattering. For determining the influence of the energy on the nature of the orbits we classify starting conditions of orbits in planes of two dimensions. All the complex basins of escape, associated with the five escape channels of the system, are illustrated by using color-coded diagrams. The distribution of time of the escape is correlated with the corresponding escape basins. The uncertainty (fractal) dimension along with the (boundary) basin entropy is computed for quantifying the degree of fractality of the dynamical system.